2015
DOI: 10.1158/1535-7163.mct-15-0074
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoma Cell Line Screen of Oncology Drugs and Investigational Agents Identifies Patterns Associated with Gene and microRNA Expression

Abstract: The diversity in sarcoma phenotype and genotype make treatment of this family of diseases exceptionally challenging. Sixty-three human adult and pediatric sarcoma lines were screened with 100 FDA approved oncology agents and 345 investigational agents. The investigational agents library enabled comparison of several compounds targeting the same molecular entity allowing comparison of target specificity and heterogeneity of cell line response. Gene expression was derived from exon array data and microRNA expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 68 publications
4
40
0
Order By: Relevance
“…34 The underlying mechanisms governing metastases in these mesenchymal cancers are not fully understood. 35 Cytotoxic agents remain first-line treatments for metastatic STS, and survival remains poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The underlying mechanisms governing metastases in these mesenchymal cancers are not fully understood. 35 Cytotoxic agents remain first-line treatments for metastatic STS, and survival remains poor.…”
Section: Discussionmentioning
confidence: 99%
“…2 At least one targeted drug, the tyrosine kinase inhibitor pazopanib, is now approved as a second-line therapy for metastatic STS. 34 Additional therapies aimed at the insulin growth factor and mTOR pathways, as well as at mutations in ALK or MET, are undergoing clinical trials. 20 …”
Section: Discussionmentioning
confidence: 99%
“…KCNN1, on the other hand, is relatively highly expressed in the neuroblastoma lines and thus clearly not only in Ewing sarcomas. A microarray analysis studying expression in several Ewing sarcoma cell lines and other sarcoma types (including RMS) shows LINGO1 is consistently and significantly up-regulated only in Ewing sarcoma (21).…”
Section: Lingo1 Is a Previously Unidentified Biomarker For Ewing Sarcomamentioning
confidence: 99%
“…63 A broader sarcoma cellular screen at NCI showed that 10/20 Ewing’s sarcoma cell lines were sensitive, while most other sarcomas were resistant, a result that paralleled the NCI 60 data (Table S1, Supporting Information). 69 The typology of Ewing’s sarcoma cell lines as distinguished by Khan et al 70 did not correlate with englerin A sensitivity, however.…”
Section: Preclinical Studiesmentioning
confidence: 92%